Black locust (Robinia pseudoacacia L.) range contraction and expansion in Europe under changing climate. (26th January 2021) - Puchałka, Radosław; Dyderski, Marcin K.; Vítková, Michaela; Sádlo, Jiří; Klisz, Marcin; Netsvetov, Maksym; Prokopuk, Yulia; Matisons, Roberts; Mionskowski, Marcin; Wojda, Tomasz; Koprowski, Marcin; Jagodziński, Andrzej M.
Abstract: Robinia pseudoacacia is one of the most frequent non‐native species in Europe. It is a fast‐growing tree of high economic and cultural importance. On the other hand, it is an invasive species, causing changes in soil chemistry and light regime, and consequently altering the plant communities. Previously published models developed for the potential distribution of R. pseudoacacia concerned 2070, and were based mainly on data from Western and Central Europe; here we extended these findings and included additional data from Eastern Europe. To fill the gap in current knowledge of R. pseudoacacia distribution and improve the reliability of forecasts, we aimed to (i) determine the extent to which the outcome of range modeling will be affected by complementing R. pseudoacacia occurrence data with sites from Central, Southeastern, and Eastern Europe, (ii) identify and quantify the changes in the availability of climate niches for 2050 and 2070, and discuss their impacts on forest management and nature conservation. We showed that the majority of the range changes expected in 2070 will occur as early as 2050. In comparison to previous studies, we demonstrated a greater eastward shift of potential niches of this species and a greater decline of potential niches in Southern Europe. Consequently, future climatic conditions will likely favor the occurrence of R. pseudoacacia in Central and Northeastern Europe where this species is still absent or relatively rare. There, controlling the spread of R. pseudoacacia will require monitoring sources of invasion in the landscape and reducing the occurrence of this species. The expected effects of climate change will likely be observed 20 years earlier than previously forecasted. Hence we highlighted the urgent need for acceleration of policies aimed at climate change mitigation in Europe. Also, our results showed the need for using more complete distribution data to analyze potential niche models. Abstract : Previously published models of R. pseudoacacia 's potential distribution concerned 2070, and were based on data from Western and Central Europe; here we extended these findings using data from Eastern Europe and 2050. We demonstrated a greater eastward shift of potential niches of this species and a greater decline in Southern Europe. Future climatic conditions will likely favor the occurrence of R. pseudoacacia in Central and Northeastern Europe. The expected effects of climate change will likely be observed 20 years earlier than previously forecasted. Also, our results showed the need for using more complete distribution data to analyze potential niche models.